0467 Benefits of CBT-I for Women Veterans with and without PTSD. (27th May 2020) - Carlson, G C; Kelly, M R; Josephson, K; Mitchell, M; Fiorentino, L; McGowan, S; Culver, N; Kay, M; Alessi, C; Washington, D L; Yano, E; Martin, J L
Abstract: Introduction: A quarter of women Veterans (WVs) receiving VA healthcare meet diagnostic criteria for both insomnia disorder and posttraumatic stress disorder (PTSD). Cognitive Behavioral Therapy for Insomnia (CBT-I) is effective at improving sleep among individuals with comorbid psychiatric conditions; however, no studies have examined the impact of CBT-I in women with insomnia plus PTSD. The current analyses examined changes in sleep symptoms, quality of life (QoL), and mental health symptoms from pre- to post-CBT-I in WVs with and without PTSD. Methods: This was a secondary analysis of 75 WVs with insomnia (32 with probable PTSD), who received CBT-I within a behavioral sleep intervention study (NCT02076165). Measures completed at baseline, posttreatment, and 3-month follow-up included: insomnia severity (Insomnia Severity Index, ISI), sleep quality (Pittsburgh Sleep Quality Index, PSQI), PTSD symptoms (PTSD Checklist-5, PCL-5; probable PTSD=total score ≥33), depressive symptoms (Patient Health Qestionnaire-9, PHQ-9), and mental and physical quality of life (Short Form Health Survey, SF-12). One sample T -tests examined changes in ISI, PSQI, PHQ-9, PCL-5, and SF-12 from baseline to posttreatment and baseline to follow-up. Two samples T -tests compared change scores in ISI, PSQI, PHQ-9, and SF-12 between participants with and without PTSD. Results: There were significant improvements in ISI ( p ≤.001), PSQI (p≤.001), PHQ-9 ( p ≤.001), PCL-5 ( p =.001), and SF-12 mental ( p ≤.001) and physical ( p =.03) from baseline to posttreatment and 3-month follow-up ( p ≤.001-.01). There were no significant change score differences between WVs with and without PTSD from baseline to posttreatment ( p =.06-.98) or 3-month follow-up ( p =.09-.93). Conclusion: CBT-I appears to be an effective treatment to improve insomnia symptoms among WVs with and without PTSD, and may reduce psychiatric symptoms as well. These findings suggest WVs with comorbid insomnia and PTSD benefit from CBT-I. The appropriate sequencing of CBT-I and PTSD treatments remains potentially important, but unstudied. Support: VA/HSR&D IIR-HX002300; NIH/NHLBI K24HL14305; VA Office of Academic Affiliations through the Advanced Fellowship Programs in HSR&D and Women's Health